Quantification and proposal of greenhouse gas reduction measures in the construction of a 220 kv transmission line. Cajamarca – Carhuamayo - Romero, Andrea (2017)
The present research work shows that for the construction of a transmission line 220 kv. from Cajamarca – Carhuamayo, was emitted to the atmosphere 4025 tons of CO2 equivalent, which leads us to think that all activity is responsible for the emission of greenhouse gases in the atmosphere Which will lead to Global Warming to lead us to Climate Change afterwards.This work was made on the basis of 2 scopes; scope 1 caused by fuel consumption and scope 2 caused by electricity consumption, from which scope 1 represents 93% to 3756 tons of CO2 compared with 7% from scope 2 with 2 269 tons of CO2 equivalent, this is due to that the main input for the development of this construction project was fuel. This makes the company to take the right measures to decrease on what is most affecting GHG emissions and focus efforts on it.